English language communicative ability at the workplace: are the students ready? / Sheema Liza Idris and Hazlin Hassan - Idris, Sheema Liza; Hassan, Hazlin (2005)
English Language Communicative ability is an important aspect for students in order for them to survive once they have graduated in order to be accepted for the workplace. We hear a lot of comments that have been put upon graduates who are left jobless, and one of the reasons is their inability in communicating in English. The argument on the inability of graduates who are incapable of communicating and using the English Language well has brought us to discuss this issue. Despite having all the compulsory English courses at the university level, graduates and business executives are still facing a lot of problems when communicating with people. No matter whether it is the basic oral skills or the writing skills, they face difficulties in expressing themselves. Thus, this study is carried out to see whether the graduating students of Diploma in Office Management and Technology (OM) of UiTM Pahang are well prepared and equipped for the workplace in terms of their English Communicative ability. It could later provide a common ground for further discussion and debate on this issue. On top of this, it could also provide feedback for the management of the university to make any decision which could lead to the improvement of the current situation.